The origin of the depressions interrupting the eastern Sierra Pampeanas broken foreland, explained by localized crustal extension through the juan Fernández ridge path, using gravimetric data. (February 2023) - Gimenez, Mario; Villegas A, Raquel J.; Richarte, Daniel; Lince Kinger, Federico; Alvarez, Orlando; Nacif, Silvina; Folguera, Andrés
Abstract: The Salinas Grandes and Salina de Ambargasta salt pans are located in the Eastern Sierras Pampeanas in the Pampean broken foreland zone, a product of the Chilean-Pampean flat subduction zone. This region constitutes an anomalously flat morphology of 350 × 150 km and occupies an extensive area in a northeast-southwest direction. These flat depressions abruptly interrupt the eastern Sierras Pampeanas morphology, burying the structure beneath Late Cenozoic-Quaternary deposits of the Andean orogenic front. We obtained from a previous model in spherical harmonics, the geometry of the Moho observing a lower crustal attenuation below the salt pan areas, which is maximum towards the north of the Salina de Ambargasta. From the Bouguer anomaly, calculated by unifying data from different sources, and its residual anomaly, we calculated the analytical signal to adjust the gravimetric anomaly's wavelength, which shows that this flat morphology follows NE to NNE gravity minima. Werner deconvolution and localized Euler deconvolution calculated from the residual Bouguer anomaly indicate that the anomalous masses are located above 15 km depth, by the wavelengths of the anomalies, presumably indicating the differential uplift of high-density rocks placed in the lower and mid-crust, following the measured crustal attenuations. Additionally, these solutions show that this NE depression is segmented by NNW structures perpendicular to the main trough. Crustal thickness attenuation is interpreted as related to the track of the Juan Fernandez Ridge beneath the eastern Pampean broken foreland sector, based on plate kinematic reconstructions. As depicted in recently released tomographic data, its tearing and related asthenospheric upwelling could have promoted lithospheric localized extension, explaining the Salinas Grandes-Ambargasta depressions that are segmenting the eastern Sierras Pampeanas at the Andean orogenic front. Highlights: The attenuated Moho correlates with the Juan Fernández Ridge trace. The morphological changes achieved in the eastern Pampean Foreland broken zone, could be explained for the JFR transit. The Salinas Grandes and Salina de Ambargasta salt pans constitute a topographic anomaly provoked by the development of the Nazca Plate.